Pengembangan Aplikasi Virtual Tour 360 Degree berbasis Web untuk Pengenalan Pura Dalem Sidakarya - Gama, Adie Wahyudi Oktavia; Kurniawan, I Nyoman Hary (LPPM STT Terpadu Nurul Fikri, 2022)
Pura Dalem Sidakarya includes the Territorial Temple, Kahyangan Tiga, or the Village Temple. The existence of Dalem Sidakarya Temple is to commemorate the services of the Brahmin Rivet. Pura Dalam Sidakarya has the Parhyangan Dalem Sidakarya architecture using its concept but still respects the predecessors of the founders of Parahyangan Jagat Bali by allocating it into one Sad Kahyangan. In addition to exploring the Sad Kahyangan Temple, there is also a Parahyangan Jagat Natha in this temple. Pura Dalem Sidakarya has a historical value, namely being the place for Pinunas Tirta Sidakarya or Tirta Penyidakarya for the success of religious activity. However, from the results of the initial survey, there are still many people who still need to learn about the existence of Pura Dalem Sidakarya. With the development of information technology today, the author built a Website-based 360 Degree Virtual Tour Application that aims to provide information and give the impression as if you are at Jagat Dalem Sidakarya by using research flow such as problem, problem formulation, literature study/material collection, system design, system design, system testing/data collection, data analysis/data validation, and conclusion. Based on the results of tests carried out using the Black Box Testing Method, all features in the application can run appropriately according to their functions.